1990
DOI: 10.1111/j.1600-0560.1990.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of nuclear inclusions in spindle and epithelioid cell nevus cells

Abstract: The nuclei of spindle and epithelioid cell nevus (SECN) cells often contain inclusions. To determine the origin and pathogenesis of the nuclear inclusions, 12 cases of SECN were electron microscopically examined. True inclusions, pseudoinclusions, and electron-lucent areas were frequently found in the nuclei of SECN cells in all cases. The true inclusions were composed of various structures including vesicles and electron-dense homogenous substance. The pseudoinclusions were a cytoplasmic structure engulfed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…Melanocytic neoplasms commonly show pseudo‐inclusions in melanocytic nuclei, on both histology and electron microscopy 14,15 . These pseudo‐inclusions appear to be in the nuclei, but contain cytoplasmic components, and are demarcated from the nuclear matrix by a nuclear membrane 15 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Melanocytic neoplasms commonly show pseudo‐inclusions in melanocytic nuclei, on both histology and electron microscopy 14,15 . These pseudo‐inclusions appear to be in the nuclei, but contain cytoplasmic components, and are demarcated from the nuclear matrix by a nuclear membrane 15 …”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the presence of pigmented organelles within the intranuclear inclusions was compatible with the hypothesis that these inclusions may have arisen for nuclear pseudo‐inclusions following the breakdown of the nuclear membrane or trapping of cytoplasmic constituents within the nucleus during atypical mitosis 18 . Sakamoto et al 15 identified true nuclear inclusions in spindle and epithelioid cell nevi (Spitz nevi) by electron microscopy. These inclusions varied in size (up to 2.4 μm in diameter), shape (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations